A networking model supporting small and medium enterprises to develop new processes and products - Harding, Stephen John (2002)
Small and Medium Enterprises (SMEs) are a key part of manufacturing economies. However, the move towards globalisation of supply can potentially be harmful to SMEs, which, because of their size and lack of internal resources, often lack the capability to add value to their products and differentiate themselves in the marketplace. Networks are seen as a key method by which SMEs can acquire "know how" on the external environment as well as in collaborating to supply customers to overcome these constraints.